Um estudo sobre a divulgação das demonstrações contábeis de organizações de direito privado do Espírito Santo : relação entre a quantidade divulgada e suas características contábeis e a percepção do elaborador quanto sua importância - Angelo, Rodolfo Amorin de (2016)
This paper aims to identify the relationship between the level of disclosure of accounting information and the accounting characteristics of the private organizations located in Espírito Santo, as well as to discover the accounting firm's perception of its importance. Using as a theoretical platform for its foundation the relevance of accounting information and the theory of disclosure, a quantitative methodology was adopted, in which it sought to verify if the characteristics of organizations such as size, leverage, the fact of being audited and, specifically, audited by a Big Four could influence the amount of published statements (proxy disclosure). In order to complement the data, a questionnaire was elaborated with the objective of conducting an exploratory research and discovering the perception of the elaborator of the accounting statement as to its importance, that is, the internal user's view of disclosure. The collected sample was composed of publications of private organizations, which published their financial statements in editions of the Official Newspaper of Espírito Santo between January 1, 2012 and December 31, 2014, making a total of 736 observations. The questionnaire was sent to all companies in the sample by e-mail (which was collected by accessing the company's CNPJ card at the Federal Revenue Service website) and linked to all of them. From the evidences found through multiple pooled linear regression, the hypothesis was accepted that the variables size of the company, the fact that it is audited and audited by a Big Four company positively influence the disclosure of the company. The leverage variable had a negative influence on the level of disclosure, the opposite of that expected for the research. Regarding the results obtained through the questionnaire it can be noted that there are many incentives for companies to publish their financial statements. Currently, many have done so due to the obligation with the legislation, highlighting the fact that the publication has a high cost and does not consider relevant the publication of the financial statements.